The Nursery Age Child. - Davids, Jenny (Karnac Books, 2010)
This book aims to facilitate the understandings of nursery age children, that is, children around three, four and five years, and their parents. Children of these ages are particularly fascinating. The wealth of their growing minds is apparent in their play and in their widening capacity to express themselves in words. It is a time of much discovery and experimentation, accompanied often by excitement and anxiety. There is something open-minded and open-hearted about children of these years. The author's views on nursery age children have been based on observing and working with them over the p.